2009
DOI: 10.1590/s1806-37132009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco e profilaxia para tromboembolismo venoso em hospitais da cidade de Manaus

Abstract: Objective: To identify and classify risk factors for venous thromboembolism (VTE) in hospitalized patients, as well as to evaluate medical practices regarding prophylaxis for the disease. Methods: An observational crosssectional study, carried out between January and March of 2006, involving inpatients at three hospitals in the city of Manaus, Brazil. Risk stratification for VTE was based on the criteria established by the Brazilian Society of Angiology and Vascular Surgery and by the International Union of An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
0
13
0
7
Order By: Relevance
“…20,21 The risk of death after an acute thrombotic event is four to eight times greater in patients with cancer than in patients without cancer and VTE is the second most common cause of death among cancer patients. 22,23 Studies by Fuzinatto et al, 6 Engerhorn et al, 7 Pereira et al, 9 Andrade et al, 10 Rocha et al 11 and Franco et al, 24 all observed that prophylaxis against VTE was under-utilized in patients in hospital, and practically all of the patients analyzed at the hospitals involved had high VTE risk, but less than half of them were given the appropriate prophylaxis. As such, the correct prophylactic measures were not taken, even in patients with potential risk factors for development of VTE and its complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 The risk of death after an acute thrombotic event is four to eight times greater in patients with cancer than in patients without cancer and VTE is the second most common cause of death among cancer patients. 22,23 Studies by Fuzinatto et al, 6 Engerhorn et al, 7 Pereira et al, 9 Andrade et al, 10 Rocha et al 11 and Franco et al, 24 all observed that prophylaxis against VTE was under-utilized in patients in hospital, and practically all of the patients analyzed at the hospitals involved had high VTE risk, but less than half of them were given the appropriate prophylaxis. As such, the correct prophylactic measures were not taken, even in patients with potential risk factors for development of VTE and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 20 years, studies have been conducted to determine the situation in Brazilian hospitals with relation to VTE prophylaxis and the findings show that among both medical and surgical patients appropriate prophylactic measures are not being taken, even when risk factors for VTE are present. [7][8][9][10][11] However, few studies have been conducted with the objective of formulating strategies and providing guidance in the form of hospital-wide thromboprophylaxis programs. 11,12 Machado 13 recommends that a multidisciplinary team should be assembled made up of people who understand the importance of pharmacological prophylaxis, in order to improve the frequency and quality of provision of VTE prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…O risco para TEV foi alto em 50,6% das internações, moderado em 18,6% das internações e baixo em 30,8% dos pacientes. Em 74% dos pacientes que apresentavam risco moderado ou alto, não se utilizou tromboprofilaxia medicamentosa 74 .…”
Section: Proposta Do National Institute For Clinical Excelenceunclassified
“…Andrade et al (2009) reported 23 risk factors for the developing of venous thromboembolism: surgery time exceeding half an hour, systemic blood pressure (SBP), major abdominal or pelvic surgery, immobilization in bed, limited ambulation, cancer, fracture of the lower limbs, varicose veins in the lower limbs, neurological disease, congestive heart failure (CHF), chronic obstructive pulmonary disease (COPD), obesity, contraceptive use, atrial fibrillation, placement of orthopedic prosthesis, hormone replacement, nephrotic syndrome, use of a central venous catheter, peripheral venous thrombosis, thrombotic disease, inflammatory bowel diseases, postoperative intensive care unit (ICU) stay and congenital heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the factors cited by Andrade et al (2009), the literature reports other risk factors, such as blood transfusion (Geerts et al, 1994), Chagas disease (Arteaga Fernández et al, 1989) and cigarette smoking (Hioki et al, 2001;Moreira et al, 2009;Pamplona et al, 1997).…”
Section: Introductionmentioning
confidence: 99%